A method for crude oil removal from empty bunches - Mokhtar, Mohd Noriznan; Sulaiman, Alawi; Samsu Baharuddin, Azhari; Gomez, Javier Hernando Chavarro; Busu, Zainuri; Yunus, Robiah (2014)
The present invention provides a method for the recovery of residual crude palm oil and its components from the biomass, such as empty fruit bunch using integration of water and steam that comprises the steps of water flooding 202, steam injection 204, steam soaking 206 and product draining 208, which are based on the following: • The use of steam to transfer the energy to water and then increases the temperature of remaining oil located within biomass • The use of water and steam to reduce the viscosity of residual oil attached to the biomass.